Dimostrare e argomentare.
y = a·e^(- 2·x) + b
LIM(a·e^(- 2·x) + b) =b
x--> +∞
y=-1 Asintoto---> b = -1
y = a·e^(- 2·x) - 1
passa per [0,0]
0 = a·e^(- 2·0) - 1---> 0 = a - 1--> a = 1
y = e^(- 2·x) - 1
{y = e^(- 2·x) - 1
{y = 3
risolvo: [x = - LN(2) ∧ y = 3]
[- LN(2), 3] intersezione
calcolo integrale:
3 - (e^(- 2·x) - 1) = 4 - e^(- 2·x)
∫(4 - e^(- 2·x) dx =
=e^(- 2·x)/2 + 4·x
x = 0 : e^(- 2·0)/2 + 4·0= 1/2
x = - LN(2):
e^(- 2·(- LN(2)))/2 + 4·(- LN(2))= 2 - 4·LN(2)
1/2 - (2 - 4·LN(2)) = 4·LN(2) - 3/2